Lung cancer therapeutics that target signaling pathways: an update. (October 2010) - Ray, M Roshni; Jablons, David; He, Biao
Claiming more than 150, 000 lives each year, lung cancer is the deadliest cancer in the USA. First-line treatments in lung cancer include surgical resection and chemotherapy, the latter of which offers only modest survival benefits at the expense of often severe and debilitating side effects. Recent advances in elucidating the molecular biology of lung carcinogenesis have elucidated novel drug targets, and treatments are rapidly evolving into specialized agents that hone in on specific aspects of the disease. Of particular interest is blocking tumor growth by targeting the physiological processes surrounding angiogenesis, pro-tumorigenic growth factor activation, anti-apoptotic cascades and other cancer-promoting signal transduction events. This article looks at several areas of interest to lung cancer therapeutics and considers the current state of affairs surrounding the development of these therapies.